Another serious misunderstanding: Jung, Giegerich and a premature requiem. Issue 1 (22nd January 2015) - Saban, Mark
Abstract: Barreto's paper, 'Requiem for analytical psychology' utilized Jung's dreams and visions to argue for the obsolescence of Jungian psychology. Its thesis rested upon the theoretical assumptions of Giegerich's psychology as a Discipline of Interiority, which he and Giegerich claim are themselves based in Jung's psychology. Here I argue that that claim is misplaced because it depends upon a fundamental misunderstanding of the nature of Jung's psychological project. I shall further argue that Giegerich's arguments for a Jungian basis to his psychology rely upon misreadings and decontextualisations of Jung's original texts. Finally, I shall attempt to draw attention to the weaknesses and contradictions involved in Barreto's interpretations of Jung's dreams and visions.